FALSE ALARM PROBABILITY IN THE MULTIPERIODICITY SEARCH - Molenda-Zakowicz, J. (Одеські астрономічні публікації, 2017)
We apply the False Alarm Probability analysis, (FAP), to the multiperiodicity search. Then we show the necessity of using the FAP method in the analysis of the astronomical time-series. We present the results obtained for 153 stars supposed or known to be pulsating variables. We examine the statistical properties of the excited frequencies and find a relation between the parameters of the fitted sine-curves and the FAP. Finally we show the application of our results to the individual stars and large samples of stars.